How to incorporate : - Diamond, Michael R. (J. Wiley, 2007)
This edition covers all the latest changes in corporation and partnership laws and includes up-to-the-minute information, advice, and guidance on every topic of concern to business owners dealing with the issues and difficulties of incorporating